Frequency of Cameroon Haplotype in a Cohort of Sudanese Patients with Sickle Cell Disease - A I Attalla, Bakhieta; A Gasim, Eltahir; E Ibrahim, Montaser (Gezira Journal of Health Sciences; Vol 11 No 1 (2015), 2015)
Background:   Haplotypes provide useful population data. The beta-globin gene cluster was the first to be described and is still one of the most studied nuclear DNA segments used for investigation of evolutionary relationships of human populations. Objective: The aim of this study was to determine the frequency of the Cameroon haplotype in a cohort of Sudanese patients with sickle cell disease. Materials and Methods : This was a prospective, cross-sectional hospital-based cohort study involving 80 sickle cell disease patients from western Sudan (38 males and 42 female) who were 3-38 years old (mean age 9.5 ± 6.1), and presented to the sickle cell clinic at the Children Emergency Hospital Khartoum between March -April 2008. Following informed consent and using a non invasive technique (buccal wash) samples were collected. DNA was extracted using the chloroform method. β S -globin gene Cameroon haplotype was determined by amplification refractory mutation system (ARMS) polymerase chain reaction technique. Primers were designed based on the published human beta globin chain sequence for known haplotype Cameroon. Results: In the 160 alleles studied β S gene was found to be linked to the Cameroon haplotype in 17 alleles 10.6% (95% confidence interval 6.31-16.47%). Eight patients were homozygous and one patient was heterozygous. Conclusion: The Cameroon haplotye has a frequency of 10.6% in this cohort of Sudanese patients with sickle cell anaemia from western Sudan. We recommend further larger study to evaluate the frequency of the different known haplotypes and a longitudinal study to correlate the haplotypes to the clinical course of the disease.